INVESTIGATION OF EYE MOVEMENTS OF SEDENTARY AND TABLE TENNIS PLAYERS - Reza Behdari; Erdal Zorba; Mehmet Göktepe; Recep Soslu; Şakir Bezci (ümit doğan üstün, 2019)
This study aimed to examine the elite level table tennis players with some visual parameters between sedentary individuals. In this study, 20 elite-level athletes playing table tennis 20 sedentary people, including 40 people participated voluntarily. All the athletes were passed through eye examinations. Besides, vision parameters were examined with pre-test and post-test. In the evaluation of the data, we used the Shapiro Wilk test to see normality assumptions. Because the data were verified to have a normal distribution, we used independent samples t-tests to examine the statistical differences. Saccadic eye movement (SGH); near the saccadic and remote saccadic test, a professional table tennis player and sedentary subjects in visual acuity and accommodation (adaptation easy to see) the level of significance in the properties (p <0.05) was adopted. When the results were analyzed, we identified that the saccadic test in table tennis players near and far with that in terms of statistically significant difference between the sedentary group (P:0,02*-T:2,35, P:0,04*-T:2,12).